2020
DOI: 10.1007/s00300-020-02650-1
|View full text |Cite
|
Sign up to set email alerts
|

Sun exposure drives Antarctic cryptoendolithic community structure and composition

Abstract: 1. DGGE profiles indicated a clear grouping of samples according by sun exposure. 2. Higher similarities were observed within samples collected in the same site. 3. Separation in abundance and community composition in response to sun exposure. 4. The F/B dominance showed a significative dominance of fungi. *Highlights (for review : 3 to 5 bullet points (maximum 85 characters including spaces per bullet point)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Although further efforts are required in future research to measure microclimatic conditions at these same nunataks, the previous works state that, inside rocks, temperature can be between 5 and 15°C above air temperature (Kirby et al, 2012;Amarelle et al, 2019), and extreme UVA and UVB values can be totally mitigated at less than 2 mm deep, even with translucent minerals (Wierzchos et al, 2015). Again, this scenario is in accordance to what has been previously described for lithic communities from other extreme environments, such as different locations within continental Antarctica, including the Antarctic Dry Valleys (De Los Ríos et al, 2007, 2014Coleine et al, 2020) and the Atacama Desert (Wierzchos et al, 2018), but in contrast to nearby Antarctic soils subjected to milder conditions, which have been described to harbor a much higher microbial diversity than rocks (Garrido-Benavent et al, 2020).…”
Section: Substrate Characteristics Also Explain Principal Differences In Microbial Community Structure and Biomarkers Distributionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although further efforts are required in future research to measure microclimatic conditions at these same nunataks, the previous works state that, inside rocks, temperature can be between 5 and 15°C above air temperature (Kirby et al, 2012;Amarelle et al, 2019), and extreme UVA and UVB values can be totally mitigated at less than 2 mm deep, even with translucent minerals (Wierzchos et al, 2015). Again, this scenario is in accordance to what has been previously described for lithic communities from other extreme environments, such as different locations within continental Antarctica, including the Antarctic Dry Valleys (De Los Ríos et al, 2007, 2014Coleine et al, 2020) and the Atacama Desert (Wierzchos et al, 2018), but in contrast to nearby Antarctic soils subjected to milder conditions, which have been described to harbor a much higher microbial diversity than rocks (Garrido-Benavent et al, 2020).…”
Section: Substrate Characteristics Also Explain Principal Differences In Microbial Community Structure and Biomarkers Distributionsupporting
confidence: 79%
“…Several Antarctic microbial taxa have developed strategies to colonize rocks as their primary niche (i.e., 'lithobionts'), following an avoidance strategy since rocks harbor a more stable environment inside (De Los Ríos et al, 2014;Yung et al, 2014;Coleine et al, 2020). Endolithic microorganisms can thus colonize different spaces within rocks: chasmoendoliths appear on cracks and fissures in contrast to cryptoendoliths, which grow on pores formed after weathering of rocks (Pointing et al, 2009;Cowan, 2014;De Los Ríos et al, 2014;Archer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We re‐analysed and compared samples collected in more than 40 sites spanning Northern and Southern Victoria Land during the XXVI and XXXI Italian Antarctic Expeditions (i.e. grouping samples according to geography as SVL, NVL and HH; see Methods), using Illumina sequencing of amplicon libraries that targeted fungal ITS region (Coleine et al ., 2018a, 2018b, 2020a, 2020b, 2020f) and bacterial 16S (Coleine et al ., 2019), to provide important insights regarding the biogeographic patterns of these microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Culturomic and high-throughput sequencing-based studies revealed a surprising prokaryotic and eukaryotic microbial diversity, with recurrent taxa exclusive to this habitat (Selbmann et al, 2005(Selbmann et al, , 2008(Selbmann et al, , 2014Adams et al, 2006;Selbmann et al, 2013a;Selbmann et al, 2013b;Egidi et al, 2014;Archer et al, 2017;Coleine et al, 2018aColeine et al, , 2019Coleine et al, , 2020bColeine et al, , 2020c. High-throughput sequencing-based studies informed that sun exposure plays a crucial role in the community composition, taxon abundance and distribution of functional groups of fungi in Antarctic cryptoendolithic communities (Archer et al, 2017;Coleine et al, 2018bColeine et al, , 2020d, affecting these ecosystems more than other abiotic parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies are elucidating the biodiversity, structure, and composition of Antarctic cryptoendolithic communities [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], including their spatial organization [ 35 ] and the influence of environmental factors (i.e., altitude and sun exposure) on shaping biodiversity and community composition of functional groups of fungi [ 36 ]. However, despite their paramount ecological importance, Antarctic endolithic communities are not well characterized in terms of their genomic repertoire and stress adaptations.…”
Section: Introductionmentioning
confidence: 99%